Introducing linguistics : theoretical and applied approaches - Garavito, Joyce Bruhn de; Schwieter, John W. (Cambridge : Cambridge University Press, 2021)
Everything we do involves language. Assuming no prior knowledge, this book offers students a contemporary introduction to the study of language. Each thought-provoking chapter is accessible to readers from a variety of fields, and is helpfully organized across six parts: sound; structure and meaning; language typologies and change; language and social aspects; language acquisition; and language, cognition, and the brain. The book's companion website also offers three brief chapters on language and computers; animal communication; and dialectal varieties of English. The chapters feature illustrative tables, figures and maps, along with three types of pedagogical boxes (Linguistic Tidbits; Pause and Reflect; and Eyes on World Languages) that break up text, contextualize information, and provide colourful accents that give real data from languages across the globe. Key words are bolded and defined in a glossary at the end of the book, while end-of-chapter summaries and practice exercises reinforce the key points discussed.
Includes bibliographical references and index.
Keywords: Linguistics; TESOL